HLA-G 3’UTR polymorphism diplotypes and soluble HLA-G plasma levels impact cervical cancer susceptibility and prognosis - Gan, Jun; Di, Xing-Hong; Yan, Zi-Yi; Gao, Yang-Fan; Xu, Hui-Hui (Frontiers in Immunology, 2022)
Background: Human leukocyte antigen G (HLA-G) is an immune checkpoint molecule with relevance in several cancers. The aim of this study was to evaluate the potential role of soluble HLA-G (sHLA-G), its genetic polymorphisms and its haplotype structure in the susceptibility and prognosis of primary cervical cancer in a Chinese Han population. Methods: We investigated sHLA-G plasma levels and 3' untranslated region (3'UTR) polymorphisms through ELISA and direct DNA sequencing, respectively, in cervical cancer patients (120 cases) and healthy control women (96 cases). The data were analysed for associations using PowerMarker, Haploview, and GraphPad Prism. Results: In this study, 8 polymorphic sites, 16 haplotypes and 23 diplotypes in the HLA-G 3'UTR were identified in our study population. We observed that each pair of 8 polymorphic sites exhibited linkage disequilibrium. The heterozygote CT genotype at position +3422 (rs17875408) was more common in cervical cancer patients than in healthy women (OR=5.285, P<0.05). Haplotypes UTR-1, UTR-3, and UTR-7 accounted for more than 85% of both groups, but no significant difference was found. The frequency of the UTR-1/UTR-3 diplotype in patients was significantly higher than that in controls (P<0.05). In addition, we further observed that HLA-G 3'UTR polymorphisms may influence the sHLA-G plasma level in patients' peripheral blood, especially 14 bp Ins/Del (rs371194629) and +3142 C/G (rs1063320). A receiver operating characteristic (ROC) curve analysis showed that the sHLA-G level had good diagnostic performance in differentiating patients with cervical cancer from healthy women (AUC>0.7). Among patients, mean sHLA-G levels increased with increasing FIGO stages but were not related to the overall survival time. Conclusions: The results of the present study enhance our understanding of how HLA-G 3'UTR polymorphisms can influence the peripheral sHLA-G plasma level and play a key role in cervical carcinogenesis. This study further confirmed that sHLA-G may represent a novel plasma biomarker for the prognosis and potential therapeutic target of cervical cancer.